A new record of three tubificid species (Annelida: Oligochaeta) from Al-Hawiezah marsh, Iraq - Jaweir, H.J. (Mesopotamian Journal of Marine Sciences, 2022)
This paper reports the first record of three species of aquatic oligochaete worms from Al-Hawiezah marsh, south of Iraq. It was evident that the specimens belonged to the family: Naididae, subfamily: Tubificinae, Species: Aulodrilus pigeuti; Embolocephalus velutinus and Limnodrilus profundicola. A. pigueti is a new record for Iraqi fauna. The study includes the identification and description of these species together with photographic illustrations of chaetal types of each species.